The Power of Affection: Exploring the Key Drivers of Customer Loyalty in Virtual Reality-Enabled Services - Yan, Jun; Ali, Ihtesham; Ali, Rizwan; Chang, Yaping (Frontiers in Psychology, 2022)
The accelerating growth of virtual reality (VR) technology and evolving customer needs make multifarious challenges and opportunities for service industries. Based on the Technology Acceptance Model and Theory of Affection Responses, we explored the key drivers of customer loyalty in virtual reality-enabled services through a large-scaled survey data collected from VR users in four major cities of Pakistan. The study employs the partial least squares structural equation modeling (PLS-SEM) approach. We verified that the authenticity of the VR experience and TAM dimensions (ease of use, usefulness of VR) are the key drivers of customer loyalty behavior in VR-enabled services. Furthermore, results revealed that Affective responses (i.e., enjoyment, emotional involvement, and flow state) significantly mediated the relationships between the drivers and customer loyalty (continued use, recommendation, willingness to pay premium). Implications for researchers and VR practitioners were also provided.